TNF- α expression on rats after Candida albicans inoculation and neem (Azadirachta indica) extract feeding - I Dewa Ayu Ratna Dewanti (Universitas Airlangga, 2011)
Background: Neem is a known traditional medicine from trees which function as immunomodulator. Candidiasis found in mouth is 80% caused by Candida albicans (C. albicans). Immunity is important to limit C. albicans since medicine price is relatively traditional medicine may become a good choice. In the other side the medicine price may not be reached by the citizen, cause citizen choose the traditional medicine. Purpose: The research is aimed to explain of TNF-α expression on rats after inoculated by C. albicans and fed with neem extract (Azadirachta Indica). Methods: There were 5 groups, the first group which was called as control group (KO) hadn't been fed aqueous extract from neem leaves and was not inoculated by C. albicans, the other group (treatment) was classified into 4 groups. The first group was inoculated by C. albicans only (KP1), second group was fed with 50 mg/day/kg body weight aqueous extracts from Neem leaves, then inoculated with C. albicans starting from day 8 until day 21 (KP2), third group was fed with 100 mg/day/kg body weight aqueous extract from Neem leaves, then inoculated with C. albicans start from day 8 until day 21 (KP3), fourth group was fed with 200 mg/day/kg body weight aqueous extract from Neem leaves, then inoculated by C. albicans start from day 8 until day 21 (KP4). The data was collected from by swabbing the rat's tongue to calculate C. albicans colonies. The rats were acclimated and collected for immunohistochemistry measurement. Results: The study showed that there were different result on ANOVA, HSD test, and linier regression. ANOVA showed significant difference (p < 0.01) between groups. The HSD test showed significant difference (p < 0.05) between each groups. TNF-α was the stimuli sensor from environment, and used as parameter to see the effect from the change of innate immunity component to C. albicans. Conclusion: Aqueous extract from neem leaves increased the macrophage TNF-α expression on in rat in oculated with C. albicans. <span style="font-family: TribuneBold; font-size: 10pt; color: #231f20; font-style: normal;